Spezialisierung des Leitungssystems des Bauunternehmens und ihre Messung - Ginevičius, Romualdas (Journal of Civil Engineering and Management, 1996)
Building enterprise management system's specialization and its measuringManagement system's specialization is the main principle of its formation. If you want to define the specialization's influence on others dimensions of this system, it is necessary to express it quantitatively.At this moment there are two types of management systems in building enterprises—functional and divisional.By this reason all system specialization subscription can find all these types which are expressed quantitatively. In this connection management specialization generalization will be of these parts geometrical mean number.Statybos įmonės valdymo sistemos specializavimas ir jo vertinimasSantrauka. Skiriami du statybos įmoněs valdymo sistemos skirstymo į skyrius būdai: pagal vykdomus darbus arba funkcijas ir pagal objektus, produktus arba patarnavimus. Funkcinį specializavimąsi galima išmatuoti atitinkamai įvertinus valdymo uždavinių dalinio specializavimo mastą: divizioninį—išmatavus funkeinį specializavimąsi divizionų viduje. Bendras valdymo sistemos specializavimosi rodiklis nustatomas paėmus minėtų dalinių rodiklių geometrinį vidurkį.Article in German.First Published Online: 26 Jul 2012